Social and Pedagogical Features of Islamic Teachings and Folk Pedagogy (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article provides information about the socio-pedagogical features of Islamic teachings and folk pedagogy. In particular, the text of the Quran was written in the 7th century, the Quran was compiled into a single book during the time of Caliph Uthman, all its other texts were destroyed, the legal values of Sharia have a social description, they are based on a number of principles, and the hadith provide commentary on the fundamentals of Islam.